2011
DOI: 10.1097/mcg.0b013e3181eeb732
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding Within Three Hours After Percutaneous Endoscopic Gastrostomy Placement

Abstract: Early tube feeding ≤3 hours after PEG placement has no significant differences to delayed or next-day feeding in respect to complications, death in ≤72 hours, or number of significant gastric residual volumes at day 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 14 publications
2
38
0
1
Order By: Relevance
“…A meta‐analysis of 5 randomized controlled trials compared early feeding after PEG placement (≤3 hours) with delayed or next‐day feeding and found no significant differences in complications, deaths in the first 72 hours, or number of significant gastric residual volumes at day 1 84 . A retrospective study examined the safety and outcomes of early feedings (≤4 hours) during a 5‐year period at a tertiary care center where the majority of PEG procedures were performed on inpatients by gastroenterologists 85 .…”
Section: Section 4 Enteral Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis of 5 randomized controlled trials compared early feeding after PEG placement (≤3 hours) with delayed or next‐day feeding and found no significant differences in complications, deaths in the first 72 hours, or number of significant gastric residual volumes at day 1 84 . A retrospective study examined the safety and outcomes of early feedings (≤4 hours) during a 5‐year period at a tertiary care center where the majority of PEG procedures were performed on inpatients by gastroenterologists 85 .…”
Section: Section 4 Enteral Accessmentioning
confidence: 99%
“…The tract begins to mature approximately 7–10 days after PEG placement, and it takes a few weeks for fusion to take place between the stomach and peritoneum. In malnourished or immunocompromised patients, this process can take longer 84 . Patients who are discharged home with a newly inserted PEG tube must be closely monitored to prevent inadvertent dislodgement.…”
Section: Section 4 Enteral Accessmentioning
confidence: 99%
“…Another proposed rationale for delayed feeding is to allow time for better sealing of the gastrostomy tract around the gastrostomy tube, thus reducing the chance of leakage of gastric contents and peritonitis (14). However, the practice of delayed feeding has been questioned in the PEG literature and multiple studies have demonstrated that early feeding, typically < 3 hours but even as soon as 1 hour after PEG, is safe (5-10). Endoscopists have argued that delayed feeding offers little benefit because bowel sounds, audible fairly soon if not immediately after PEG placement, indicate normal function (7).…”
Section: Discussionmentioning
confidence: 99%
“…The overall success and complication rates are comparable between the two percutaneous techniques and both are used routinely in oncology patients (3-4). While several studies have shown that feeding can safely be initiated in select patients < 3 hours following PEG tube placement (5-10), at many centers, patients are admitted to the hospital for observation and are not fed for 12 to 24 hours following PFG placement (11-13). This study was done to evaluate the feasibility and safety of early feeding following outpatient PFG placement in oncology patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring gastric residual volumes is no longer recommended in critically ill medical patients. Furthermore, a study by Szary et al 54 found that feeding ≤3 hours after PEG placement showed gastric residual volumes were not increased within the first 24 hours compared with delayed feedings. Feeding early after PEG placement does not appear to increase the risk of aspiration.…”
Section: Feeding After Tube Placementmentioning
confidence: 99%